Komunikasi Estetik Dalam Visual Lukisan Karya I Wayan Pengsong - I Nyoman Subudiartha; Sasih Gunalan; Susi Handayani (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
The occurrence of dialogue between artists, works of art, and devotees, makes works of art become an important medium in a communication process. The communication process that occurs in the activity of interpreting works of art is called aesthetic communication. The term aesthetic communication is an option in the activity of interpreting the use of a work of art. Although a work of art is a personal expression of every artist, after the work is born, it will become a form that is ready to be enjoyed by the art public. To capture the value contained in existing works of art, the aesthetic communication process is very important, as we can see in I Wayan Pengsong's painting. One of the strengths of Pengsong's painting lies in his efforts to build and record various aspects of the culture on the island of Lombok as the subject matter of his work. The aesthetic communication process in Pengsong's painting is in the process of using the cultural and visual values ​​that exist in the artist's work, which is presented in a work. The process of meaning that exists in Pengsong's works is handed back to all appreciation in an effort to interpret and give meaning to these works, based on various aspects of the process of interpreting the works of art.